Análise proteômica quantitativa em ameloblastomas - Sara Ferreira dos Santos Costa (2020)
Ameloblastoma is a benign epithelial odontogenic tumor characterized by slow but locally aggressive growth, high morbidity and great potential for recurrence. Despite the advances in bioinformatics that led to the development of technologies that allowed the study of omics sciences, there are scarce studies of proteomics in ameloblastomas. Our aim was to perform a quantitative analysis of the proteomic profile of ameloblastomas compared to dental follicles. In the present study, we performed shotgun proteomics to identify proteins using the combination of liquid chromatography and tandem mass spectrometry (LC-MS/MS). We also performed cluster and functional enrichment analyses of proteins with altered abundances in ameloblastomas. This study also carried out an assessment of the BRAF mutation status in cases of ameloblastoma. Finally, the validation of the results of the proteomics step was performed using immunohistochemistry. Quantitative comparative proteomic analysis resulted in the identification of 1,343 proteins. Ameloblastomas were shown to harbor a proteomic profile distinct from that found in dental follicles, with 33 over-regulated and 21 down-regulated proteins. Overregulated proteins are involved in glucose metabolism and biosynthesis pathways, indicating an adaptative tumor growth mechanism. Most of the down-regulated proteins play prominent roles in cellular mitochondrial energy production and oxidoreductase metabolism regulation, suggesting mitochondrial dysfunction and oxidative stress response. BRAF p.V600E was detected in most ameloblastomas and it may be related to the induction of glycolytic flux, as well as oxidative stress. To investigate the activation of the antioxidant system, we assessed the immunoexpression of the antioxidant enzyme glutathione S-transferase omega 1 (GSTO1), which was up-regulated in ameloblastomas. Ameloblastomas showed diffuse and moderate to strong GSTO1 immunoexpression, whereas weak or negative imunoexpression was observed in dental follicles. We hypothesize that ameloblastoma presents metabolic reprogramming towards a more glycolytic state with high biosynthetic precursor generation. In addition, a low abundance of mitochondrial respiratory components possibly associated with mitochondrial dysfunction was observed. We were able to identify for the first-time alterations in critical metabolic pathways, which not only contribute to the elucidation of ameloblastoma pathogenesis but also could be potential targets for drug therapy in these tumors.